Analize kakovosti sadik izbranih gozdnih drevesnih vrst v letih 2019, 2020 in 2021 - Železnik, Peter (Gozdarski vestnik, 2021)
Rapid climate changes, resulting in exceptional weather phenomena, increasingly endanger Slovenian forests. Larger forest areas become exposed in disasters, damages of the reproductive crown parts arise, and due to the changed climate conditions, the reproduction of the forest trees is disrupted. Using well thought-over completion of the natural regeneration with the artificial one we can increase the resilience of the forests to future disasters and using genetically varied reproduction material we can increase the adaptive potential of young stands. The basis for a successful artificial regeneration is formed by high-quality and site-adapted seedlings. Using low-quality seedlings or even seedlings of an unsuitable provenience can cause long-term negative consequences. Between the years 2019 and 2021, we performed measurements of seedlings of seven tree species on nine locations in Slovenia in the framework of the project %Estimation of the Success of Forest Regeneration by Planting and Sowing in Slovenia% (CRP V4-1819). Estimating the quality of seedlings, we used directly visible and measurable features. We performed a general check-up of seedlings and then we measured height and root collar diameter, assessed the root system asymmetry and noticeable deformations. In beech seedlings of equal age, we noticed differences in height, diameter, and height/root collar diameter index. Thereby, the beech seedlings whose GRM was acquired from the same GSO differed regarding the planting location. The younger and non-transplanted pedunculate oak seedlings were lower in average, however, they had a larger root collar diameter than a year older seedlings and transplanted seedlings. We assume this is the reflection of the transplantation stress. Seven years old sycamore maple had expectedly larger root collar diameter, however, they were considerably lower than four years younger seedlings. Additionally, the sycamore maple seedlings, whose forest reproductive material (FRM) was acquired from the same forest seed object (FSO), varied in size on one planting location to a larger extent than on the other one. Among all monitored parameters, the height/root collar diameter index as a relative measurement appears to be a good parameter, since it proved to be a sufficiently good quality index even in a limited data range. Thereby we must consider the parameters like the height of the seedlings and root collar diameter. Assessment of the root system asymmetry proved to be a very subjective method. For assessing the quality of seedlings based on measurable marks we would need orientational parameter values as the ones experimentally ascertained for spruce seedlings.
Keywords: gozdovi; kakovost sadik; obnova gozdov; sadike; sajenje